PENINGKATAN KETERAMPILAN MENULIS PARAGRAF DESKRIPSI MELALUI TEKNIK PENGAMATAN OBJEK LANGSUNG PADA SISWA KELAS IV C SDN PAKIS V SURABAYA - Desi Eka Pratiwi (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
Writing skills are one of several basic language competencies that students must have in order to be skilled at communicating in writing. However, in learning Indonesian, the writing aspect in class IV C is still relatively low. Based on these problems, the purpose of this research is to increase student activity in learning to write descriptive paragraphs and improve skills in writing descriptive paragraphs. This study uses Classroom Action Research (CAR) procedures which consist of four series of activities in each cycle (1) planning, (2) action, (3) observation, and (4) reflection. The results of this study showed an increase from cycle I and cycle II, student activity in cycle I reached 72%, while in cycle II it increased to 82%. Classical mastery in writing paragrah description skills in cycle I reached 32.26% and in cycle II increased to 83.87%. From the results of this study it can be concluded that the use of direct object observation techniques can improve the skills of writing descriptive paragraphs in class IV C SDN Pakis V Surabaya.